Recruitment challenges in stroke rehabilitation randomized controlled trials: a qualitative exploration of trialists' perspectives using Framework analysis. (August 2020) - McGill, Kris; McGarry, Jodie; Sackley, Catherine; Godwin, Jon; Nicoll, Avril; Brady, Marian C
Objective: To explore the underlying reasons for recruitment difficulties to stroke rehabilitation randomized controlled trials from the perspective of trialists. Design: A qualitative study using semi-structured interviews and Framework analysis. Participants: Twenty multidisciplinary stroke rehabilitation trialists across 13 countries with a range of clinical and research experience. Methods: Twenty semi-structured telephone interviews were carried out. Purposeful sampling ensured a range of opinions were gathered from across the international stroke rehabilitation research community. Using Framework analysis, the analytical framework was formed by three researchers and tested before being applied to the total dataset. Results: Three themes described the trialists' perception of the underlying reasons for recruitment difficulties: (i) decision making, (ii) importance of recruiters and (iii) a broken system. Trialists described frequently disregarding evidence in favour of prior research experiences when planning randomized controlled trial recruitment. All felt that the relationship between the research and clinical teams was vital to ensure recruiters prioritized and found value in recruitment to the trial. Experienced trialists were frustrated by the lack of reporting of the reality of running trials, research governance demands and the feeling that they had to deliberately underestimate recruitment timeframes to secure funding. Conclusion: Stroke rehabilitation trialists described recruitment difficulties which may be related to their experiential based recruitment decision making, a lack of understanding of how best to incentivize and maintain relationships with recruiters and unrealistic bureaucratic expectations both in terms of gaining funding and research governance.